2019
DOI: 10.1126/sciadv.aaw3896
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic presentation of noncanonical Wnt5a motif promotes mechanosensing-dependent differentiation of stem cells and regeneration

Abstract: Noncanonical Wnt signaling in stem cells is essential to numerous developmental events. However, no prior studies have capitalized on the osteoinductive potential of noncanonical Wnt ligands to functionalize biomaterials in enhancing the osteogenesis and associated skeleton formation. Here, we investigated the efficacy of the functionalization of biomaterials with a synthetic Wnt5a mimetic ligand (Foxy5 peptide) to promote the mechanosensing and osteogenesis of human mesenchymal stem cells by activating noncan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 49 publications
4
74
1
Order By: Relevance
“…Amri et al (2013) discussed the mechanical and thermal properties of polypropylene composites reinforced with CTS fiber and it was concluded that addition of CTS improved the Young's modulus, thermal stability, and impact strength of composites [39]. Li et al (2019) investigated the bio functionalization of biomaterials with synthetic Wnt5a mimetic ligand (Foxy5 peptide) to enhance the osteogenesis and mechanosensing of human mesenchymal stem cells by stimulating noncanonical Wnt signaling. They found that immobilized Wnt5a mimetic ligand-activated noncanonical Wnt signaling leading to enhanced intracellular calcium level, F-actin stability, actomyosin contractility, and cell adhesion structure development [40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amri et al (2013) discussed the mechanical and thermal properties of polypropylene composites reinforced with CTS fiber and it was concluded that addition of CTS improved the Young's modulus, thermal stability, and impact strength of composites [39]. Li et al (2019) investigated the bio functionalization of biomaterials with synthetic Wnt5a mimetic ligand (Foxy5 peptide) to enhance the osteogenesis and mechanosensing of human mesenchymal stem cells by stimulating noncanonical Wnt signaling. They found that immobilized Wnt5a mimetic ligand-activated noncanonical Wnt signaling leading to enhanced intracellular calcium level, F-actin stability, actomyosin contractility, and cell adhesion structure development [40].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2019) investigated the bio functionalization of biomaterials with synthetic Wnt5a mimetic ligand (Foxy5 peptide) to enhance the osteogenesis and mechanosensing of human mesenchymal stem cells by stimulating noncanonical Wnt signaling. They found that immobilized Wnt5a mimetic ligand-activated noncanonical Wnt signaling leading to enhanced intracellular calcium level, F-actin stability, actomyosin contractility, and cell adhesion structure development [ 40 ]. Kang et al (2019) suggested that macrophages play a significant role in regulating foreign body response in biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…The bio‐functionalization of developed biomaterials was conducive to further enhance its bioactivity. It is well known that surface nanostructures or decoration of bioactive motifs could regulate cells behaviours, and greatly improve the potential of cell differentiation, which is the key factor to the success of the implanted scaffolds 17,44,45 . For example, a noncanonical Wnt5a motif could functionalize biomaterials in enhancing the osteogenesis and associated skeleton formation 44 .…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the bioactive molecules for precisely regulating TE‐PTG growth or PTH secretion can be investigated based on related signal pathways, for instance, polypeptides that can promote cell adhesion and proteins that can regulate Ca 2+ and Pi. Sometimes, bioactive molecules can be bond to material design (Li et al, 2019) or produced by multicell coculture (Cui et al, 2020), which will be further described in Section 6. Despite the kind of molecules, the dosage, incorporation ways, and releasing are essential to be considerate (Koons & Mikos, 2019).…”
Section: Te‐ptgsmentioning
confidence: 99%
“…It has been proved that lots of cells like to bind to RGD and the materials designed with RGD showed a greater cell growth behavior (Lee et al, 2012; Liu et al, 2012; Park, Joung, Park, Lee, & Lee, 2008; Wilsona, Liliensieka, Murphyc, Murphyb, & Nealey, 2012; Zaviskova et al, 2018). Li et al used Foxy5, a mimetic hexapeptide of the Wnt5a signal path, combined with RGD to provide a stronger mechanosensing and osteogenesis biomaterial network for hMSC differentiation (R. Li et al, 2019). Kang et al formed the dimer of RGD and bisphosphonate‐coated gold nanoparticles to regulate macrophages' adhesion to the material (Kang et al, 2019).…”
Section: Regulatory Strategiesmentioning
confidence: 99%